2006
DOI: 10.1007/s00572-006-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza alter the concentration of essential oils in oregano (Origanum sp., Lamiaceae)

Abstract: The effect of root colonization by Glomus mosseae on the qualitative and quantitative pattern of essential oils (EO) was determined in three oregano genotypes (Origanum sp.). To exclude a simple P-mediated effect through mycorrhization the effect of P application to plants on the EO accumulation was also tested. In two genotypes the leaf biomass was increased through mycorrhization. Root colonization by the arbuscular mycorrhizal fungus (AMF) did not have any significant effect on the EO composition in oregano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
116
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(140 citation statements)
references
References 21 publications
18
116
1
1
Order By: Relevance
“…G. etunicatum inoculated mint and oregano (Origanum vulgare) plants had increased growth and nutrient contents (Karagiannidis et al, 2012). The positive effect of AMF root colonization by G. mosseae on shoot biomass of oregano plants raised in greenhouse has also been reported by Khaosaad et al, (2006). Sharma et al, (1998) found highest root colonization of 16% in apple crop in Manali and lowest in Kotgarh region.…”
Section: II 400x 40supporting
confidence: 57%
“…G. etunicatum inoculated mint and oregano (Origanum vulgare) plants had increased growth and nutrient contents (Karagiannidis et al, 2012). The positive effect of AMF root colonization by G. mosseae on shoot biomass of oregano plants raised in greenhouse has also been reported by Khaosaad et al, (2006). Sharma et al, (1998) found highest root colonization of 16% in apple crop in Manali and lowest in Kotgarh region.…”
Section: II 400x 40supporting
confidence: 57%
“…Observations in mycorrhizal A. annua suggest that the increase in artemisinin concentration may not be entirely attributed to enhanced P nutrition (Chaudhary et al 2008;Kapoor et al 2007). Khaosaad et al (2006) also found that essential oil concentration significantly increases in two oregano genotypes associated with G. mosseae, but the levels of essential oil in plants treated with P are not changed, which indicates that the increase in essential oil concentration in mycorrhizal oregano plants is not due to an improved P nutrition, but directly depends on association with the AM fungus.…”
Section: Mechanism By Which Am Symbiosis Promotes Secondary Metabolismentioning
confidence: 87%
“…Appetitanregend, promoting digestion, antibacterial effect Khaosaad et al 2006 Origanum vulgare Appetitanregend, promoting digestion, antibacterial effect…”
Section: Mentha Arvensismentioning
confidence: 99%
“…Few reports are available about the effects of AM fungi on the production of essential oils in a limited choice of lamiaceous species. A relation between the presence of AM fungi, increased growth, essential oil accumulation, and improved mineral uptake was reported for Mentha arvensis (Khaliq & Janardhanan 1997;Gupta et al, 2002;Freitas et al, 2004). Khaosaad et al (2006) showed that G. mosseae increases the concentration of essential oils in two genotypes of O. vulgare but not in P-fertilized nonmycorrhizal plants.…”
Section: -mentioning
confidence: 77%
“…A relation between the presence of AM fungi, increased growth, essential oil accumulation, and improved mineral uptake was reported for Mentha arvensis (Khaliq & Janardhanan 1997;Gupta et al, 2002;Freitas et al, 2004). Khaosaad et al (2006) showed that G. mosseae increases the concentration of essential oils in two genotypes of O. vulgare but not in P-fertilized nonmycorrhizal plants. Moreover, in a comparative analysis of the effects induced by three AM fungi, Copetta et al, (2006) found that inoculation with Gigaspora rosea Nicolson & Schenck BEG 9 increased biomass, root branching and length, and total amount of essential oil in basil O. basilicum L. and that increased oil yield was associated to a significantly larger number of peltate glandular trichomes (main sites of essential oil synthesis) in the basal and central leaf zones.…”
Section: -mentioning
confidence: 77%